Brexit Means Brexit: What Does It Mean for the Protection of Third-Party Victims and the Road Traffic Act?. (31st March 2017) - Marson, James; Ferris, Katy; Nicholson, Alex
Abstract: The UK's referendum decision of 23 June 2016, where voters elected to leave the European Union (EU), will fundamentally change aspects of national law. Much debate has focused on the constitutional implications of the decision and the procedure by which the government seeks to facilitate the exit. Further, issues of substance including the part played by immigration and the control of the UK's borders have also dominated legal and political commentary. Yet there has been no critical examination of the effects it will have on motor vehicle insurance law. The statute governing much of the law (the Road Traffic Act 1988), along with the extra-statutory agreements providing protection for the third-party victims of negligent uninsured drivers and untraced vehicles, is each profoundly influenced by EU directives. Given the Brexit decision and the resolution of the government to facilitate the UK's exit of the Union, we argue that the protective rights for such victims of motor accidents are likely to be reduced. Further, the advancement of the law, developed through the jurisprudence of the Court of Justice, will be lost.